Fußball und Feminismus Eine Ethnografie geschlechterpolitischer Interventionen - Faust, Friederike (Verlag Barbara Budrich, 2019)
Is football still a man´s sport? For decades, Europe´s most popular sport was considered a male domain without question. This changed recently with an increasing number of women claiming their rights and spaces, and criticizing misogyny. This ethnographic study accompanies the local and international activists of a women´s rights and women´s football NGO, and explores the possibilities, challenges and constraints that arise out of the friction between football and feminism.